Indeterminacy and the Regulation of Task Allocation: The Shape of Support Roles in Healthcare. (15th March 2012) - Kessler, Ian; Heron, Paul; Dopson, Sue
Abstract Drawing upon Marsden's typology of employment systems, this article explores how the indeterminacy of the employment relationship is enacted and resolved in relation to the healthcare assistant (HCA), a key work role in the delivery of nursing care in a hospital setting. It suggests that the regulation of task allocation within nursing assumes a hybrid form, requiring further analysis of the influences shaping the HCA role. Based on multi‐method hospital case studies, the article distinguishes different types of HCA, explaining their emergence by reference to the interaction between organizational structure and personal agency. The article illustrates the value of Marsden's framework, and by addressing its limits in a healthcare setting seeks to develop a deeper understanding of task allocation in different workplace employment systems.